Determination of two-dimensional space-time correlations in jet flows using simultaneous PIV and LDV measurements - FITZPATRICK, JOHN AIDAN (My University, 2010)
The two-dimensional space-time turbulence statistics of free shear jet flows in the form of the two-point velocity correlation tensor are important for aeroacoustic noise source modelling based on the acoustic analogy approach. This paper presents a direct application of the Point Referenced Global Correlation (PRGC) technique to measure the components of this correlation tensor for a sector of the flow field in two jet configurations. The PRGC approach combines single point and global measurement techniques and enables two-point space-time correlations over a region of the flow to be obtained. The technique is applied to a single stream jet and a co-axial coplanar jet at a Mach number of 0.24 using commercial Laser Doppler velocimetry (LDV) and low-speed Particle Image velocimetry (PIV) systems. Results for the 1-D correlations are shown to compare well with two point measurements. The results for the 2-D space time correlations are presented and the characteristics for both configurations discussed.
PUBLISHED
Keywords: Mechanical & Manufacturing Engineering